Distribution characteristics of vaginal flora and pregnancy outcomes in cervical incompetence patients - LI Xue; XIAO Yi; ZHANG Hong (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To investigate the distribution characteristics of vaginal flora in patients with cervical incompetence (CIC), and the effect of cervical cerclage on pregnancy outcome in patients with CIC with abnormal vaginal flora.Methods·A total of 1 261 pregnant women participated in the study. According to the diagnosis, they were divided into cervical incompetence group (CIC group) and normal pregnancy group (NP group). The CIC group patients randomly received cervical cerclage (CIC-C group) or expectation therapy (CIC-E group). Vaginal secretion samples of the patients in the groups were collected and analyzed in the laboratory. Meanwhile, through the results of vaginal flora, the CIC-C group and CIC-E group were further divided into normal vaginal flora groups (CIC-C-N group and CIC-E-N group) and abnormal vaginal flora groups (CIC-C-A group and CIC-E-A group). All groups were processed accordingly and analyzed on pregnancy outcomes. T-test and Chi-squared test were used for comparison between the groups, and One-way ANOVA was used for comparison among the three groups. Statistical significance was accepted at a value of P<0.05.Results·Among 1 261 vaginal secretion specimens, the positive rate of pathogenic bacteria was 22.0% (277/1 261). The pathogen detection rates in the CIC group and NP group were 32.9% (229/696) and 8.5% (48/565). Twenty-three types of vaginal flora were detected in the CIC group, and 9 were detected in the NP group. The proportions of women who had term birth were 75.94% in the CIC-C group, 70.03% in the CIC-E group, and 87.79% in the NP group (P=0.000). Compared with the CIC-C-A group, the CIC-E-A group had a lower term delivery rate (61.84% vs 77.78%, P=0.011) and a higher incidence of pregnancy complications (22.37% vs 9.15%, P=0.006).Conclusion·There are differences in the distribution and diversity of vaginal flora between CIC patients and normal pregnant women. Cervical cerclage can improve pregnancy outcomes in CIC patients with abnormal vaginal flora.